'Becoming experts': learning through mediation - Abdul Rahim, Fauziah (UUM College of Arts and Sciences, 2009)
Purpose – This study is largely founded on Vygotsky’s sociocultural theory, Feuerstein’s theory of Mediated Learning Experience and Lave and Wenger’s ‘community of practice’, which concerned building a community of learners that places mediation as central in learning and teaching. While the overall study involved Malaysian Year One English and Mathematics classrooms, this article focuses only on the latter. Two research questions were posed: 1) How does the teacher/peers mediate learning? 2) How does mediation influence the individual’s identity? Method – This qualitative study was conducted within a period of three months. Data collection included intense classroom observations, interviews, classroom discourse and dialogic discussions with teachers and pupils. Microgenetic analyses of transcripts were made to show moment-to moment changes observed.Findings – Four types of mediation emerged from the data : Environmental mediation, cognitive mediation, affective mediation and metacognitive mediation (i.e., an ECAM model for mediation).Findings suggest that mediation enabled the Mathematics teacher to change, to take ownership and to sustain her new pedagogical approaches within the classroom. This re-focusing benefited her pupils, and dramatically changed a particular less able pupil from one who was initially ‘lost in his world,’ into one who was able to engage in the learning process, take ownership of his own learning, as well as mediate other pupils’ learning. Value – Hence it is argued that the ECAM model for mediation provided opportunities for this teacher and her pupil to expand their capacity to learn and develop their identities as individuals capable of learning and becoming ‘experts’.